SOCIODEMOGRAPHIC, HEALTH AND SERVICES CHARACTERISTICS USED BY HOSPITALIZED ELDERLY - Fernandes Furquim, Renata Cristini; Andreani Cabral, Luciane Patricia; Lima, Melina Lopes; Blanski Grden, Cloris Regina; Fadel, Cristina Berger [UNESP]; Bordin, Danielle (Univ Federal Estado Rio De Janeiro, Programa Pos-graduacao & Enfermagem, 2021)
Objective: to analyze elderly individuals from different age groups admitted to a teaching hospital, according to sociodemographic characteristics, health and services used. Methods: cross-sectional study, with 158 elderly hospitalized in a university hospital, with dependent variable the age: individuals from 60 to 70 years and more than 70 years; and as an independent variable: sociodemographic, health and service used conditions. Data were analyzed by the Fisher's Exact and chi-square tests. Results: patients older than 70 years had significantly lower level educational, absence of spouse, presence of multimorbities, longer hospitalization, ICU hospitalization and need to help with daily living at home, to than the younger people (p<0.05). Conclusion: knowledge of the differences between the different age groups made it possible to understand the fragilities of each group and fostered important questions for understanding the sociodemographic, health and services context used by this population.
Keywords: Aged; Health profile; Health services; Tertiary healthcare; Hospitalization